Risk Characteristics and Response Strategies for Marine Pollution Due To Container Ship Accidents at PT IPC Terminal Petikemas - Lira Agusinta; Peppy Fachrial; Cindy Herawati; Syalwa Divan (Dinasti Review, 2025)
Export-import and international trade activities require the role of container ships and ports. Shipping and port activities that do not meet standards can cause marine pollution and ship accidents. The number of incidents of pollution brought on by container ship accidents rises as a result of mechanical issues like inclement weather and human mistake as well as the continued decline in container accidents.This research is a literature study or literature review research. This research uses a systematic literature review approach regarding the application of risk characteristics and response strategies in cases of container ship pollution and accidents. By implementing a risk characteristics program and response strategies that are carried out regularly, accidents that occur on container ships can be minimized. By conducting a comprehensive review of marine pollution and implementing a risk characteristics program and response strategy, its effectiveness can be proven to reduce the level of marine pollution and ship accidents.